Getting up to mischief: Comic sensibility, generational and national identity in Arthur Mathews's comedy writing. Issue 1 (1st March 2022) - Free, Marcus
Best known as co-writer of Channel 4 sitcom Father Ted (1995‐98), Irish writer Arthur Mathews is among the most versatile in recent British and Irish television comedy. Mathews's other British work includes sketch show Big Train (1998‐2002), Toast of London (2013‐15) and Toast of Tinseltown (2022‐present), while his work for Irish television includes the sitcom Val Falvey TD (2009). Drawing on interviews with Mathews concerning his formation and development as a writer, this article situates his distinctive comic sensibility within Ireland's changing social and cultural landscape from the 1960s to the 1980s and the east coast of Ireland's unusual 'mediascape' as a confluence of Irish, British and American currents. Mathews's career and work illustrate how comic sensibility, national and regional identities intersect in the 'British Isles' as a geo-cultural archipelago rather than a collection of distinctive national identities. The article examines how he relates his acutely surreal humour and love of generic and stylistic incongruity to his formative experiences of watching and absorbing British television from a vantage point both 'outside', in a different national jurisdiction, and culturally on its margins. Finally, it gauges the limits of Mathews's work in offering forms of cultural and social critique through comedy.